Bridging management control systems and innovation: the evolution of the research and possible research directions - Barros, R. S.; Ferreira, A. (Qualitative Research in Accounting and Management, 2019)
Purpose: The purpose of this study is to present the evolution of thinking on the role of management control systems (MCSs) in innovation, according to the development of control practices, and to provide a reflection on the achievements of the more recent literature. Design/methodology/approach: This paper assesses articles, books and book chapters that have explored MCSs in innovation, together with seminal works on management accounting and control. Findings: Moving from the traditional phase where MCSs were seen as detrimental to innovation, the literature has now reached a new consensus that attributes a positive role to control. In this recent phase, it arises from the literature that MCSs in the realm of innovation should embrace a multiplicity of controls; MCSs depend on the magnitude and innovation mode of a company; MCSs evolve over time; and that synergies and tensions are expected to arise. Adding these factors to the inherent complexity of innovation, the assertion is that qualitative approaches should be undertaken to infuse the field with more fine-grained evidence. It is also proposed that this methodological approach be used to address the following points: (1) the use of multiple controls; (2) synergies and tensions; and (3) behavioural aspects of controls in relation with innovation. Originality/value: The paper is of value for researchers who have an interest in studying the use of MCSs in innovation and in qualitative research and proposes some areas of research that could be explored.